The Link and Match between the Competency of Vocational High Schools Graduates and the Industry on CAD/ CAM and CNC - Wibisono, Galih; Wijanarka, Bernardus Sentot; Theophile, Habanabakize (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
This study describes (1) the work process analysis of the production stage in the industry, (2) the required competency and skills of CAD/ CAM and CNC in the industry, (3) the implementation of the basic competency of CAD/ CAM and CNC in vocational high schools, (4) the link and match between the competency of vocational high schools graduates and the industry on CAD/ CAM and CNC. The descriptive-qualitative method was employed by involving 8 people from Mega Andalan Kalasan Ltd (MAK) and 5 people from vocational high schools. The data were collected through observation and interviews which were further analyzed descriptively. The findings indicate (1) the work process analysis map the competencies that must be owned by the workforce including CAD drafter, CAM programmer, and CNC operators in which each workforce involved 4 work process sequences, (2) the competency of CAD/ CAM and CNC described the knowledge and psychomotor activities. In detail, the activity of the CNC machine setting produced knowledge competence and the skills of 36.5% and 26.7% respectively. The operating CNC machine produced the knowledge competence and skills of 25.4% and 23.3% respectively. The 3D drawing and 2D CAD systems produced the knowledge competence and skills of 19% and 23.3% respectively, CAM Programming generated the knowledge competence and skills of 19% and 26.7% respectively, (3) the implementation of basic competencies can be categorized as good, (4) there are two competencies fulfilled the link and match between the vocational high schools' competencies and industry, namely manufacturing drawing competency with CAD as well as mechanical competency with CNC and CAM.